2014
DOI: 10.1111/jsr.12146
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and the risk of work injury: a Swiss case–control study

Abstract: SUMMARYSleep problems are a well-known risk factor for work injuries, but less is known about which vulnerable populations are most at risk. The aims of this study were to investigate the association between sleep quality and the risk of work injury and to identify factors that may modify the association. A case-control study including 180 cases and 551 controls was conducted at the University Hospital in Basel, Switzerland, from 1 December 2009 to 30 June 2011. Data on work injuries and sleep quality were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
2
26
2
Order By: Relevance
“…In addition, the National Health Interview Survey revealed that short sleep duration (less than 6 h) increased risk of injuries [15]. A study of cases admitted to hospital due to a moderate to severe work injury indicated that poor sleep quality which resulted from short sleep duration or long duration of working was related to work injury of any type [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the National Health Interview Survey revealed that short sleep duration (less than 6 h) increased risk of injuries [15]. A study of cases admitted to hospital due to a moderate to severe work injury indicated that poor sleep quality which resulted from short sleep duration or long duration of working was related to work injury of any type [16].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep problems or poor sleep behaviors have been identified as risk factors for injury because they may impair motor function, mood, and cognitive functions through sleepiness, fatigue, and cognitive impairment [ 6 , 7 ]. Recent studies suggest that individuals with more poor sleep behaviors have significantly higher injury rates and more injury-prone behavior [ 8 , 9 ]. Several aspects of sleep behaviors may be hypothesized in relation to injury.…”
Section: Introductionmentioning
confidence: 99%
“…Short sleep (<6 hours/day) has reported associations with obesity, T2DM, hypertension, CVD and the incidence of work‐place and road traffic accidents . The physiological and metabolic pathways connecting poor sleep to CVD and T2DM are well described and were recently articulated by Reutrakul and Van Cauter .…”
Section: How Much Sleep Do We Need?mentioning
confidence: 99%